2015
DOI: 10.1017/s1368980015000282
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a government-subsidized supermarket in a high-need area on household food availability and children’s dietary intakes

Abstract: Objective: To assess the impact of a new government-subsidized supermarket in a high-need area on household food availability and dietary habits in children. Design: A difference-in-difference study design was utilized. Setting: Two neighbourhoods in the Bronx, New York City. Outcomes were collected in Morrisania, the target community where the new supermarket was opened, and Highbridge, the comparison community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 29 publications
8
136
0
1
Order By: Relevance
“…In New York City, Elbel and colleagues assessed the impact of a new supermarket on household food availability and children’s dietary intake and did not find any consistent changes in either outcome. 19 Both studies, however, had small sample sizes, limited measures of dietary intake, and few measures of contextual factors and additional outcomes that might explain or illuminate their findings, for example, what was sold at new markets, how people used them, and whether other neighborhood stores changed.…”
Section: Introductionmentioning
confidence: 99%
“…In New York City, Elbel and colleagues assessed the impact of a new supermarket on household food availability and children’s dietary intake and did not find any consistent changes in either outcome. 19 Both studies, however, had small sample sizes, limited measures of dietary intake, and few measures of contextual factors and additional outcomes that might explain or illuminate their findings, for example, what was sold at new markets, how people used them, and whether other neighborhood stores changed.…”
Section: Introductionmentioning
confidence: 99%
“…This includes longitudinal studies that: (1) move beyond retail food outlet type as a proxy to include observed measures of the food environment; (2) are based on larger and more socioeconomically diverse samples with more variability in the neighborhood food environment; (3) account for change over time in environmental features that may influence energy expenditure or otherwise confound food environment-BMI relationships over time; (4) incorporate food shopping and purchasing behaviors—such as those included in the USDA’s National Household Food Acquisition and Purchase Survey—as a mediator in food environment-BMI associations; and (5) assess other objectively measured health outcomes such as blood pressure (Zenk, Thatcher, et al, 2014). Quasi-experimental studies that evaluate naturally occurring changes in the neighborhood food environment, such as those supported by the Pennsylvania Fresh Food Financial Initiative and the federal Healthy Food Financing Initiative, are also a valuable direction for additional research (Cummins, Flint, & Matthews, 2014; Cummins, Petticrew, Higgins, Findlay, & Sparks, 2005; Elbel et al, 2015; Mayne, Auchincloss, & Michael, 2015; Wrigley, Warm, & Margetts, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…However, the sheer number of fast-food-type restaurants and convenience-type stores relative to large grocery stores in Houston might overwhelm any potential for positive dietary influence of large grocery stores on dietary intake if mere exposure plays a role in consumption choices. Taken together with results from intervention studies suggesting that the addition of a large grocery store to a food desert does not alter the dietary intake of local residents, 7,8 these results may suggest a similarly limited role for interventions involving large grocery stores in directly affecting dietary behaviors among African-American adults in Houston, Texas. However, a study in South Carolina suggested that grocery stores affected FV intake indirectly via shopping frequency and subjective perceptions of healthy food availability.…”
Section: Discussionmentioning
confidence: 65%